POTASSIUM SOIL TEST CALIBRATION FOR CORN ON TYPIC HAPLUDOX CIGUDEG - SUBIKSA, I GUSTI MADE; SABIHAM, SUPIYANDI (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2009)
Soil testing calibration is a process to provide meaning of soil test value in term of crops response. Research on soil testing calibration for corn has been carried out on Typic Hapludox Cigudeg. The objectives were: 1) to determine critical point of soil test value of K, 2) to determine the application rate of K fertilizer recommendation. The split plot design was used with consisted five rate of K fertilization on three K soil status as the main plots. There were four K soil test methods assessed to determine the critical point value for corn. K availability was classified into three categories namely low, medium, and high class. The results revealed that critical value of four soil testing methods for low, medium, and high respectively were : HCl 25% (<14, 14-29, and >29 mg 100 g-1), NH4OAc pH 7(<84 ppm, 84-220 ppm, and >220 ppm), Morgan (<70 ppm, 70-180 ppm, and >180 ppm), and Mechlich I (<54 ppm, 54-135 ppm, and >135 ppm). K fertilization significantly affected to corn plant height in the low soil K status until the rate of 60 kg K ha-1 (116 kg KCl ha-1). Dry biomass significantly increased due to K fertilization on low, medium as well as high soil K status. K fertilization also improved corn grain production. The ears of corn could not develop without K fertilization. This was an evidence that K nutrient has an important role in enzyme activity and assimilate translocation. Even with low rate of K fertilization, corn has succeeded to form ears and kernels. In the low soil K status, K fertilization sharply increased dry grain, but in the medium soil K status the curve was gentler. Whereas in the high soil K status, K fertilization did not significantly affect the dry grain yield. The recommended application rate of K fertilizationfor corn on Typic Hapludox Cigudeg with low K status was 89 kg K ha-1 and in the medium status was 53 kg K ha-1. Whereas in the high soil K status, no K fertilization was needed.